Marginal Discrepancies of Monolithic Zirconia Crowns: The Influence of Preparation Designs and Sintering Techniques. Issue 3 (27th January 2019) - Ahmed, Walaa Magdy; Abdallah, Mohamed‐Nur; McCullagh, Anthony P.; Wyatt, Chris C.L.; Troczynski, Tom; Carvalho, Ricardo M.
Abstract: Purpose: The marginal fit is an essential component for the clinical success of prosthodontic restorations. The aim of this study was to investigate the influence of different abutment finish line widths and crown thicknesses on the marginal fit of zirconia crowns fabricated using either standard or fast sintering protocols. Materials and Methods: Six titanium abutments were fabricated for receiving zirconia molar crowns. Crowns were designed virtually and milled from partially sintered zirconia blanks and divided into 12 groups (n = 10/group). Crowns in groups 1 to 6 were sintered by standard sintering, while those in groups 7 to 12 were sintered by fast sintering. Groups were further categorized according to abutment finish line and crown thickness: G1/G7 (0.5 mm chamfer, 0.8 mm thick); G2/G8 (0.5 mm chamfer, 1.5 mm thick); G3/G9 (1.0 mm chamfer, 0.8 mm thick); G4/10 (1.0 mm chamfer, 1.5 mm thick); G5/G11 (1.2 mm chamfer, 0.8 mm thick); G6/G12 (1.2 mm chamfer, 1.5 mm thick). The marginal gaps were assessed at 8 locations using digital microscopy. The linear mixed effect model analysis was performed at a significance level of 0.05. Results: All vertical marginal gaps were within the clinically acceptable range (∼11‐52 μm). G8 (FS, 0.5 mm chamfer, 1.5 mm thick) demonstrated the largest gaps (47.95 μm, 95% CI: 44.57‐51.23), whereas G3 (SS, 1.0 mm chamfer, 0.8 thick) had the smallest marginal gap (14.43 μm, 95% CI: 11.15‐17.71). A linear mixed effect models showed significant differences for the interaction between finish line × crown thickness × sintering (F = 18.96, p < 0.001). The lingual surfaces showed the largest gaps in both sintering protocols, while the mesial and mesiobuccal surfaces demonstrated the smallest gaps. Conclusions: There was a significant interaction between finish line widths, crown thickness, and sintering protocol on the marginal gaps in both sintering protocols; 1.0 mm finish line preparations with either 0.8 mm or 1.5 mm occlusal reduction had better marginal fit in both sintering protocols compared to 0.5 mm or 1.2 mm finish lines. Smaller marginal discrepancies were observed for standard sintering crowns with a 0.5 mm finish line and 1.5 mm occlusal reduction. Conservative occlusal reduction should be accompanied with a 1.2 mm finish line to obtain better marginal fit for full‐contoured zirconia crowns.